Development and validation of an improved LC-MS/MS method for the quantification of desloratadine and its metabolite in human plasma using deutrated desloratadine as internal standard - M Saquib Hasnain; Shireen Rao; Manoj Kr. Singh; Nitin Vig; Manish Kr. Singh; Subodh Kr. Budakoti; Abdulla Ansari (Journal of Pharmacy and Bioallied Sciences, 2013)
Purpose: For the determination of desloratadine (DES) and 3-OH desloratadine (3-OHD) in human plasma using deutrated desloratadine (DESD5) as internal standard (IS), a novel stability indicating liquid chromatography-tandem mass spectrometric method was developed and validated to support the clinical advancement. Materials and Methods: The solid-phase extraction method used for sample preparation and calibration range was 100-11,000 pg/ml, for which a quadratic regression (1/x 2 ) was best fitted. The blank plasma was screened and observed free from any endogenous interference. Results: The accuracy (% nominal) at low limit of quantification LLOQ level for DES and 3-OHD was 100.4% and 99.9% whereas precision (%CV) was 4.6 and 5.1%. They (DES and 3-OHD) were stable in human plasma after five freeze-thaw cycles, at room temperature for 23.8 hour, bench top stability for 6.4 hour. Conclusion: This method fulfills all the regulatory requirements for selectivity, sensitivity, precision, accuracy, stability, goodness of fit, and ruggedness of the method for the determination of DES and 3-OHD in human plasma.